Antibiotic use and knowledge in the community of Yemen, Saudi Arabia, and Uzbekistan - Belkina, Tatyana; Al Warafi, Abdullah; Hussein Eltom, Elhassan; Tadjieva, Nigora; Kubena, Ales; Vlcek, Jiri (Journal of infection in developing countries, 2014)
INTRODUCTION: Inappropriate use of antibiotics has resulted in a dramatic increase of antimicrobial resistance in developing countries. We examined knowledge, attitudes, and practices of antibiotic use in three Asian countries. METHODOLOGY: A nationwide cross-sectional study of teachers in large cities of Yemen, Saudi Arabia, and Uzbekistan was conducted. A random sample of 1,200 teachers was selected in each country. Data were collected through a questionnaire-based survey and then analyzed using descriptive and multivariate statistical methods. RESULTS: The prevalence of non-prescription antibiotic use ranged from 48% in Saudi Arabia to 78% in Yemen and Uzbekistan. Pharmacies were the main source of non-prescribed antibiotics. The most common reasons for antibiotic use were cough (40%) and influenza (34%). Forty-nine percent of respondents discontinued antibiotics when they felt better. Although awareness of the dangers of antibiotic use correlated inversely with self-medication, understanding of the appropriate use of antibiotics was limited. CONCLUSIONS: The prevalence of antibiotic self-medication in the educated adult population in the studied countries was found to be alarmingly high. Effective strategies involving regulatory enforcement prohibiting sales of antibiotics without prescription should be implemented along with educational interventions for health professionals and the public.
Keywords: Surveys and Questionnaires; Saudská Arábie; Yemen; Humans; městské obyvatelstvo; Uzbekistán; lidé středního věku; léky bez předpisu; Influenza, Human; Uzbekistan; samoléčba; Jemen; Saudi Arabia; Female; mladý dospělý; dospělí; věkové faktory; zdraví - znalosti, postoje, praxe; lidé; Urban Population; antibakteriální látky; průzkumy a dotazníky; Adult; Faculty; chřipka lidská; Self Medication; ženské pohlaví; Anti-Bacterial Agents; Developing Countries; Male; akademický sbor; Middle Aged; Drug Resistance, Bacterial; Nonprescription Drugs; Cough; Cross-Sectional Studies; Young Adult; stupeň vzdělání; bakteriální léková rezistence; Health Knowledge, Attitudes, Practice; kašel; Age Factors; mužské pohlaví; průřezové studie; Educational Status; rozvojové země